2011
DOI: 10.1002/polb.22212
|View full text |Cite
|
Sign up to set email alerts
|

Hydration‐mediated effects of saccharide stereochemistry on poly(N‐isopropylacrylamide) gel swelling

Abstract: To shed new light on the mechanisms of saccharide stereochemistry effect on macromolecules in aqueous solutions, we studied the effect of three monosaccharide stereoisomers, glucose, galactose, and mannose, on the swelling of Poly(N‐isopropylacrylamide) (PNIPA) hydrogels. We equilibrated PNIPA hydrogels in sugar solutions of different concentrations at 25 °C, and determined gel volume and mass swelling ratios, and sugar concentration imbalance. The volume‐phase‐transition occurred at molal concentrations of 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…They observed that the swelling of polyacrylamide gels, which are hydrophilic polymers as PEGs, increases with rising glucose concentrations and there is an enthalpically favorable interaction between glucose and polyacrylamide [4]. However, based on their results, sugars exert shrinkage and soluting-out effects on poly(N-isopropylacrylamide) gels, which are hydrophobic polymers as PPG [6]. These observations are in close agreement with the results of the present study of the carbohydrates soluting effects on aqueous polymer solutions.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…They observed that the swelling of polyacrylamide gels, which are hydrophilic polymers as PEGs, increases with rising glucose concentrations and there is an enthalpically favorable interaction between glucose and polyacrylamide [4]. However, based on their results, sugars exert shrinkage and soluting-out effects on poly(N-isopropylacrylamide) gels, which are hydrophobic polymers as PPG [6]. These observations are in close agreement with the results of the present study of the carbohydrates soluting effects on aqueous polymer solutions.…”
Section: Resultssupporting
confidence: 90%
“…Livney et al [4,6] studied the effect of carbohydrates on the swelling of polyacrylamide and poly(N-isopropylacrylamide) gels. They observed that the swelling of polyacrylamide gels, which are hydrophilic polymers as PEGs, increases with rising glucose concentrations and there is an enthalpically favorable interaction between glucose and polyacrylamide [4].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of saccharide on the LCST of PNIPAM were therefore explained by their effects on the structured water around the polymer. They may immobilize water molecules near them, weaken hydrophobic hydration of the polymer, and consequently enhance the hydrophobic interaction between the polymer chains . The different ability of different saccharides to lower LCST was related with the number of equatorial hydroxyl groups in the saccharide molecules, because the equatorial hydroxy groups of saccharide molecules interact more easily with water clusters around the hydrophobic isopropyl groups and thus change the situation of polymer hydration …”
Section: Introductionmentioning
confidence: 99%
“…In this context, it is worth studying the specific effect of this biologically relevant sugar on the collapse of PNIPAM-based architectures. The PNIPAM-watertrehalose ternary system is much less investigated both experimentally and numerically as compared to any other ternary system of the same polymer, including those containing saccharides [44][45][46][47][48][49]. Experimental investigations using cloud point measurements, differential scanning and isothermal titration-microcalorimetry [44,46], report a significant decrease of LCST of PNIPAM chains in aqueous solution on increasing mono-and disaccharide concentration, finding a good correlation of the saccharide hydration with the decrease of LCST, and hence with the promotion of the globular compact state of the polymer.…”
Section: Introductionmentioning
confidence: 99%